Specific Vibration Of A FluidConducting Toroidal Shell - Toyirov Gayrat Fozilovich; Jurayev Shukhrat Isroilovich (Genius Journals, 2024)
In this work, the problem of specific vibration of the fluid-conducting toroidal shell is solved. The object of the research is to evaluate the ideal fluid and the composite toroidal shell with rheagogic properties, their characteristic (or special) vibrations and dynamic characteristics. Research methods. The integral differential equations with eigenvalues are reduced to the system of ordinary differential equations. To solve these equations, freezing method, separation of variables method, Muller's method, and Godunov's orthogonal projection methods were used. The reliability of the obtained results is based on the correct formulation of the spectral limit problem, the rigor of the derived mathematical expressions, the use of based solution methods and the evaluation of the accuracy of the solutions, as well as comparisons with the solutions of other mathematical
Keywords: toroidal; shell; ideal fluid; composite material